(untitled) (Conferencea, 2022)
Food security implies that people may consume the ingredients they need for an active and healthy lifestyle at any time, in any quantity or variety. As a result, it should be mentioned that in the process of globalization, it has become vital to provide high-quality, low-cost food to the country’s population. Food is one of the most important factors in human survival. Customers seek high-quality, risk-free products. We commonly define "safe food" as high-quality, environmentally friendly, devoid of GMOs (genetically modified organisms), and free of potentially harmful food-related variables such as pesticides. This article examines the current food security issues.